Debt Maturity And Stock Returns: An Inter-Sectoral Comparison Of Malaysian Firms - Wei, Theng Lau; Siong , Hook Law; Md Nassir, Annuar (Asian Academy of Management (AAM), 2016)
This firm-level study examines whether the effects of financial leverage on stock returns of 12 Bursa Malaysian sectors can be explained by debt maturity. When total leverage is used, only 3 out of 12 sectors exhibit a significant relationship with stock returns. However, when the leverage is divided by using short-term and long-term debt, regressions in 9 out of 12 sectors reveal that either form of disaggregated leverage exhibits a significant relationship with returns at least at a 5% significance level. The results suggest that the return-leverage relationship could be indirect in terms of maturity. The panel regressions also show that sector-specific analysis is more meaningful and practical due to the mixed relationship identified. The empirical conclusions are further supported by using two indicators of financial leverage, i.e. book leverage and market leverage. The results are robust when the firm and the time effects are taken into consideration